ANALYSIS OF PATIENT SAFETY CULTURE IN SULTAN AGUNG ISLAMIC DENTAL HOSPITAL - Arbianti, Kusuma; Prakasa, Suprayogi Yoga (Odonto : Dental Journal, 2021)
Background: Health care facilities are complex organizations and must have development strategies to improve the quality of services. Service quality management must be integrated with elements of risk management and patient safety. Patient safety culture reflects a perception, norms and behavior related to the culture of preventing medical errors when serving patients. Patient safety culture is a product that results from individual or group values, attitudes, perceptions, competences and behavior patterns. Sultan Agung Islamic Dental Hospital has been operating since 2019 and has been accredited in 2020. This study aims to analyze the culture of patient safety at the Sultan Agung Islamic Dental Hospital Semarang.Method: This research method used descriptive observational study. Data collected by distributing questionnaires (onsite crosssectional survey) with Hospital Survey of Patient Safety Culture (HSOPSC) adopted from Agency for Healthcare Research and Quality (AHRQ) 2.0 version to all health workers at the Sultan Agung Islamic Dental Hospital Semarang.Result: The level of reliability of each dimensions of patient safety culture were teamwork 89.3%, staff and work speed 73%, organizational learning for continuous improvement 82.3%, response when an error occurs 69%, supervisor supports patient safety 86%, Communication about the occurrence of errors 96.3%, communication openness 85.5%, the number of error reports 39%, Hospital management supports patient safety 75.7, Change of tasks and transition 85%.Conclusion: The lowest level of reliability of patient safety culture was the dimension of the number of error reports.